Two persons and have a total sum of . First, gives of what he has to . Then gives of what he now has back to . If the ratio of the final amount of person to the final amount of person is , what was the initial amount that person had?
Similar problems:
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let the initial and end amounts A and B have be a 0 and b 0 , and a 1 and b 1 . Then a 0 + b 0 = a 1 + b 1 = 3 2 0 .
Since a 1 b 1 = 2 3 , ⟹ a 1 + 2 3 a 1 = 3 2 0 ⟹ a 1 = 1 2 8 and b 1 = 1 9 2 .
Then we have:
{ b 1 = 0 . 8 ( 0 . 2 a 0 + b 0 ) a 1 = 0 . 8 a 0 + 0 . 2 ( 0 . 2 a 0 + b 0 ) ⟹ 0 . 1 6 a 0 + 0 . 8 b 0 = 1 9 2 ⟹ 0 . 8 4 a + 0 . 2 b 0 = 1 2 8 . . . ( 1 ) . . . ( 2 )
From 4 × ( 2 ) − ( 1 ) : 3 . 2 a 0 = 3 2 0 ⟹ a 0 = 1 0 0 .